Polar-direct-drive experiments at the National Ignition Facility. (May 2016) - Radha, P B; Hohenberger, M; Marshall, F J; Michel, D T; Bates, J; Boehly, T R; Collins, T J B; Craxton, R S; Delettrez, J A; Dixit, S N; Edgell, D H; Frenje, J A; et al.
Abstract: Polar-direct-drive experiments at the National Ignition Facility (NIF) are being used to validate direct-drive-implosion models. Energy coupling and fast-electron preheat are the primary issues being studied in planar and imploding geometries on the NIF. Results from backlit images from implosions indicate that the overall drive is well modeled although some differences remain in the thickness of the imploding shell. Implosion experiments to mitigate cross-beam energy transfer and preheat from two-plasmon decay are planned for the next year.